2019
DOI: 10.1016/j.scitotenv.2018.09.236
|View full text |Cite
|
Sign up to set email alerts
|

Examining effects of ontogenic microplastic transference on Culex mosquito mortality and adult weight

Abstract: Microplastics (MPs) continue to proliferate and pollute aquatic and terrestrial environments globally. The impacts of MP pollution on ecosystems and their functioning remain poorly quantified, with most research hitherto focusing on marine ecosystems. There is a paucity of information on the impacts of MPs in freshwater ecosystems, despite the broad range of pathways through which MPs can proliferate and the extensive range of species which actively ingest MPs in these systems. Of particular interest are organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 40 publications
7
20
0
1
Order By: Relevance
“…Microplastics continue to proliferate across the biosphere, with ecological implications frequently unknown (Carlos de Sá et al, 2018;Mason et al, 2018;Sighicelli et al, 2018;Wagner and Lambert, 2018). In the present study, we further demonstrate active uptake of MPs through filtering by larval mosquitoes (Al-Jaibachi et al, 2018a, 2018b. Furthermore, we demonstrate that MPs can be transferred and retained trophically from filter feeding organisms to higher predators, and that trophic transference relates to consumption rates.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Microplastics continue to proliferate across the biosphere, with ecological implications frequently unknown (Carlos de Sá et al, 2018;Mason et al, 2018;Sighicelli et al, 2018;Wagner and Lambert, 2018). In the present study, we further demonstrate active uptake of MPs through filtering by larval mosquitoes (Al-Jaibachi et al, 2018a, 2018b. Furthermore, we demonstrate that MPs can be transferred and retained trophically from filter feeding organisms to higher predators, and that trophic transference relates to consumption rates.…”
Section: Discussionsupporting
confidence: 66%
“…It is probable that colonists are naïve to potential risks of MPs to fitness. However, Al-Jaibachi et al (2018a) found that MPs have little influence on the survival and fitness of Culex mosquitoes across their life history. Whilst this is the first study to quantitatively link MP transfer with predation rates, work is required to further explore potential trophic accumulation of MPs, alongside behavioural implications, and to discern the potential for aerial dispersal of MPs by freshwater insects aside from mosquitoes (Al-Jaibachi et al, 2018b).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on MPs tend to be divided into those looking for evidence of ingestion and those looking at the impact of the MP on some aspect of the organism's biology, with mixed and sometimes conflicting results [16][17][18][19][20]. While the majority of studies have focused upon MP particles, those which focus upon MPFs have found similar results with good evidence for ingestion in marine crustaceans, Orchestia gammarellus, Carcinus maenas, Carcinus aestuarii and Nephrops norvegicus [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%